Beyond Bacteria: Bacteriophage-Eukaryotic Host Interactions Reveal Emerging Paradigms of Health and Disease - Chatterjee, Anushila; Duerkop, Breck A. (Frontiers in Microbiology, 2018)
For decades, a wealth of information has been acquired to define how host associated microbial communities contribute to health and disease. Within the human microbiota this has largely focused on bacteria, yet there is a myriad of viruses comprising the microbiota as well, the most abundant being bacteriophages that infect bacteria. Animal hosts are colonized with niche specific microbial communities where bacteria are continuously co-evolving with phages. Bacterial growth, metabolic activity, pathogenicity, antibiotic resistance, interspecies competition and evolution can all be influenced by phage infection, and the beneficial nature of some interactions suggests that, to an extent, phages are tolerated by their hosts. With the understanding that phage-specific host-microbe interactions likely contribute to bacterial interactions with their mammalian hosts, phages may also impact aspects of mammalian health and disease that are unrecognized. Here, we review recent progress in understanding how bacteria acquire and tolerate phage in both pure culture and within complex communities. We apply these findings to discuss how intra-body phages interact with bacteria to influence their eukaryotic hosts through potential contributions to microbial homeostasis, mucosal immunity, immune tolerance and autoimmunity.